The Art of Modeling Mechanical Systems - Pfeiffer, Friedrich; Bremer, Hartmut; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
The papers in this volume present rules for mechanical models in a general systematic way, always in combination with small and large examples, many from industry, illustrating the most important features of modeling. The best way to reach a good solution is discussed. The papers address researchers and engineers from academia and from industry, doctoral students and postdocs, working in the fields of mechanical, civil and electrical engineering as well as in fields like applied physics or applied mathematics.
Keywords: Mechanical engineering; Engineering mathematics; Engineering -- Data processing; Mathematical models; Electrical engineering; Civil engineering; Mechanical Engineering; Mathematical and Computational Engineering Applications; Mathematical Modeling and Industrial Mathematics; Electrical and Electronic Engineering; Civil Engineering